Analisis Kemampuan Menyelesaikan Masalah Matematis Pada Materi Pecahan Di Kelas IV SD - Diana Ermawati; Irsyad Fardani; Dika Nurunnaja; Aulia Ulfatun Ni'mah; Devina Dwi Astuti (Universitas Majalengka, 2023)
Education is a journey and effort taken by someone in learning to pursue knowledge through understanding, solving problems, and various interesting discussions in the world of education. The purpose of this study was to analyze students' learning abilities in learning fractions. This type of research is descriptive qualitative, the subject of this research consists of 6 students of class IV SDN 1 Bae using a purposive technique. Data collection techniques using observation, interviews and documentation. The results obtained in this study are in accordance with the results of previous studies which also show that most of the student errors are related to the subject understanding index, students do not understand questions about fractional material. Subsequent studies have shown the same thing, that students tend not to be able to solve problems properly, so they still need a lot of practice. The conclusion from this study is that students tend not to fully understand fractional material so that more intensive discussions need to be carried out with the teacher or various discussion methods such as peer tutors with friends so that children do not hesitate to ask questions when experiencing difficulties.Keywords: problem solving skills, fractions, mathematics, learning difficulties, mathematics.